Klastre – nástroj pre zvyšovanie inovačnej výkonnosti a konkurencieschopnosti regiónov - Zaušková, Anna (Communication Today, 2025)
Slovakia, as well as other European countries in the last decade, tries to increase its innovation effectiveness. One of the tools used to increase the effectiveness and competitiveness is to create a cluster as a form of partnership. The scientifi c work also focuses on the clustering. In the fi rst part of this scientifi c work the theoretical basis and opinions of the authors focusing on clusters and cluster initiatives are shown. The analytical study of creation of Wood-processing Cluster in the region of Banská Bystrica (BBK) is the second part of the scientific work.